Graphene derivative coated QCM-based gas sensor for volatile organic compound (VOC) detection at room temperature - Gupta, M. (Institute of Advanced Engineering and Science, 2020)
Volatile organic compounds (VOCs) affect our daily life through their emission from very common sources such as plants, building materials, paints, pesticides, and fossil fuel burning. The detection of VOCs at room temperature is a prime requirement. The graphene-based gas sensor has the potential to detect these VOC gases due to its attractive features such as high mobility and large surface area. In this work, a graphene-derivative is prepared as a sensing material in order to detect acetone. The thin film of graphene-derivative is prepared by a drop-cast method on a quartz crystal microbalance (QCM) sensor followed by drying in the room environment conditions. The prepared graphene-derivative and thin films are characterized structurally and morphologically by standard microscopic techniques such as FESEM, EDX, and Raman spectroscopy. The electrical parameters such as mobility and resistivity are measured using Hall-effect measurements at room temperature. The response and recovery time of the graphene-derivative based 10 MHz QCM sensor are found to be 23 s and 20 s, respectively. This highly sensitive graphene-based gas sensor with good reversibility can be employed for human health and environment safety applications. Copyright Â© 2020 Institute of Advanced Engineering and Science. All rights reserved.